O efeito de instrução e feedback sob o comportamento de abordagem policial a veículos - AMORIM, Graziela Serra (2024)
The concept of feedback has been defined as a verbal, written, or vocal description of performance, providing information about the quality or quantity of someone's behavior. Most human behaviors are acquired through instructions. Instructions, advice, recommendations, suggestions, warnings, orders, among others, are used to teach, inform and describe behaviors in the most diverse situations. One of the approaches most used by military police officers during overt work is approaching vehicles. The lack of standardization of procedures for its execution can cause a series of risks to police officers, suspects and people close to them. The main objective of the research was to analyze a behavioral intervention model to adequately approach vehicles, in addition, it sought to identify whether instruction in conjunction with feedback is more effective in reducing approach errors than feedback alone and modeling and install behavioral repertoire for approaching vehicles. The design used was the single-subject version of type A-B-A-B. The experiment was carried out at the Metropolitan Policing Command of the Southern Area of the Military Police in São Luís, Maranhão, with four volunteer police officers divided into two pairs of participants. The procedure consists of the following steps: (A) baseline of vehicle approach behaviors. In sequence (B), a pair was given instructions on approaching vehicles, and then their action during the approach was recorded by video. Afterwards, they received corrective feedback in case of error and congratulations in case of success. For pair two, their action during the approach was only recorded by video and corrective feedback was provided in case of error or congratulations for their correct action (B). There was then a return to baseline (A) without intervention, and later a new intervention (B). After three months, the follow-up was produced. The data was collected by the researcher between the months of July and December 2023. The results obtained showed a progressive increase in the target behavior scores of the police officers from both teams. In intervention one, the police officer responsible for team one's security reached the maximum score of 100% correct from the second approach of intervention one, and the person responsible for the personal search in the third and team two reached the maximum score in the third approach of intervention one. The results were maintained after three months. It is concluded that both procedures were effective, with a small variation in the acquisition of correct answers in favor of the feedback+instruction combination.